Evaluasi dan Perancangan Model Bisnis Usulan pada Batik Cirebon HDM dengan Business Model Canvas (BMC) - Nurhalimah, Zhafiirah; Hasun, Farda; Chumaidiyah, Endang (Universitas Pahlawan Tuanku Tambusai, 2024)
Batik Cirebon HDM is one of a fashion business in Cirebon Regency that provides various batik products, namely batik fabrics, men's shirts, and women's blouses. Currently, Batik Cirebon HDM is experiencing difficulties to increase turnover and achieve the desired sales target of around Rp80,000,000 per month. The problem is caused by several factors, namely the number of competitors in the sales area, the types of products and batik motifs which are less varied, as well as promotional activities that have not been carried out intensely and the limited channel of Batik Cirebon HDM. To overcome these problems, it is necessary to evaluate the current business components and then make improvements simultaneously with the Business Model Canvas (BMC) method. The data needed for this research are current business model data, customer profile data, and business environment data. Evaluation of the current business model is carried out with 7 questions analysis and SWOT analysis to design a proposed strategy. The proposed strategy is to expand the reach of individual customers, add channels through Instagram and Shopee marketplace, and develop batik product innovations and services in the form of custom design of batik clothes and batik learning service. From the results of the proposed strategy, the calculation of estimated incremental revenue and costs as the impact of proposed business model is then carried out. The change of business model is feasible when sales can be increased by 15%. The suggestion for the next research is doing the desirability validation to ensure that the change of business model can be implemented.